Climate-smart agricultural practices by smallholder cocoa farmers in the semi-deciduous forest agro-ecological zone of Ghana - Philip Antwi-Agyei; Vincent Yaw Nkrumah Eloh; Prince Opoku Nti; Nartey Christian Amarh; Thelma Phoebe Owusu (Discover Sustainability)
Abstract Climate-smart agricultural (CSA) practices hold great prospect in managing climatic risks faced by smallholder tree crop farmers in sub-Saharan Africa. However, the perspectives of smallholder tree crop farmers have often been ignored, and this hampers the development of appropriate policy interventions in advancing the adoption of CSA practices by tree crop farmers. This study sought to; (i) determine the perceived impacts of climate change and variability on cocoa production, (ii) identify the CSA practices adopted by smallholder cocoa farmers; and (iii) assess the key barriers to CSA implementation in the Asante Akim South Municipality, Ghana. The study used a mixed-methods approach with data collection involving 150 household surveys and 3 focus group discussions. The CSA practices and barriers affecting their implementation by smallholders were ranked using the Relative Importance Index (RII) and Problem Confrontation Index (PCI), respectively. Results revealed that climate change and variability have impacted negatively on smallholders’ farming systems, with reduced cocoa yields, death of cocoa trees and increased post-harvest losses being amongst the adverse impacts. Integrated pest management (RII = 0.977), crop diversification (RII = 0.942) and using weather and climate information services (RII = 0.883) were ranked as the first, second and third most used CSA practices, by the smallholders in withstanding the adverse impacts of climate change and variability. Results also showed that the key barriers to the successful implementation of CSA practices included the high cost of farm inputs (PCI = 579), incidences of pest and diseases (PCI = 569) and insufficient and unsustainable government support (PCI = 544). These findings highlight the need for the Government of Ghana through the Ministry of Food and Agriculture to scale-up efforts, and significantly support smallholder tree crop farmers with both resources and technical expertise to overcome these barriers.